Teaching Writing to Different Age Groups - Begizova Madina (International Journal on Integrated Education, 2022)
The goal of teaching writing in foreign language is to form students' communicative competence, which includes knowledge of written signs, spelling of words, vocabulary and grammar, composition of written texts, the ability to create various types of written messages, mastery of the content and form of written speech, ways to express thoughts in writing. Writing acts as a means of forming and developing many skills and abilities. Thanks to exercises in writing, the student always consciously operates with his skills and abilities. He learns to understand how he constructs his speech. As well as, it develops the speech to a higher level. In this article the author defines the essence of writing and peculiarities of teaching it in different age groups.